The Use of Kahoot! Application to Increase Students’ Motivation in Learning English - Darmawan, Dedy; Abduh, Amirullah; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2025)
The results of the research revealed that the use of the Kahoot! application in learning English in non-formal education is the right thing because in addition to being effective in gamification and technology-based learning, it can also attract motivation to learn English in course institutions or non-formal education. The innovations or novelty that can be found in this research compared to previous research are because previous similar research conducted research in formal schools which are indeed mandatory for all students to follow, while this study was conducted in non-formal schools by looking at the status of a course community by relying on registration and acceptance of new students and their workforce. In how a course community can survive and maintain its existence through the quality of its teaching and learning, one of which is by using the Kahoot! application to increase students' motivation to learn English.